Partnering with traditional Chiefs to expand access to cervical cancer prevention services in rural Zambia. Issue 3 (16th January 2019) - Kapambwe, Sharon; Mwanahamuntu, Mulindi; Pinder, Leeya F.; Chisele, Samson; Chirwa, Susan C.; Parham, Groesbeck P.
Abstract: Objective: To evaluate how the influence of traditional Chiefs can be leveraged to promote access to cervical cancer prevention services in rural Zambia. Methods: A retrospective review of outcome data was conducted for all screening outreach events that occurred in Zambian Chiefdoms between October 4, 2015, and October 3, 2016. Members of the health promotion team of the Cervical Cancer Prevention Program in Zambia visited local Chiefs to inform them of the importance of cervical cancer prevention. The local Chiefs then summoned adults living within their Chiefdoms to assemble for cervical cancer prevention health talks. Screen‐and‐treat services were implemented within each of the Chiefdoms over a 1‐week period. Results: VIA‐enhanced digital imaging of the cervix (digital cervicography) was offered to 8399 women in ten Chiefdoms as part of a village‐based screening (VBS) program. In all, 419 (4.9%) women had positive screening test results. Of these women, 276 (65.8%) were treated immediately with thermocoagulation and 143 (34.1%) were referred to provincial government hospitals to undergo either the loop electrosurgical excision procedure/large loop excision of the transformation zone (n=109, 26.0%) or punch biopsy (n=34, 8.1%). Conclusion: The influence of traditional Chiefs was leveraged to facilitate access to cervical cancer prevention services in rural Zambia. Abstract : Partnering with traditional Chiefs can promote access to cervical cancer prevention services in rural Zambia.